Revisiting water resources management in the Mandara Mountains - Diane Madomguia; Esther Laurentine Nya; Emma Laureane Njomou-Ngounou; Nadège Gatcha-Bandjun; Tulinave Burton Mwamila; Jules Balna; Emina Halimassia; Jules Metsebo; Wilfried Arsène Letah Nzouebet; Raoul Rodrigue Tchoumbe; André Firmin Bon; Willis Gwenzi; et al. (Heliyon)
This article evaluates the prospects for rainwater harvesting (RWH) as a means of optimizing water management in the Mandara Mountains. RWH is a small-scale water conservation approach for locally intercepting and storing rainfall before it enters the usual hydrologic cycle. This ancient practice has recently sustained lives in semiarid areas of the world (e.g. Brazil, China), but is not yet really used in the Mandara Mountains of Cameroon where people are still lacking safe drinking water. Recently, RWH was also demonstrated as the missing puzzle in integrated water resources management (IWRM) not only in areas facing water scarcity. The present article aims to prepare large scale RWH in the Mandara Mountains. Water harvesting yields are estimated for residential roofs, administrative and confessional buildings, and agricultural areas (e.g. farm scale). The results show that RWH is an affordable, applicable, and attractive tool for both rural and urban communities to sustainably solve the long-lasting problem of lack of safe drinking water in the Mandara Mountains. Moreover, despite the short rainy season, RWH may provide enough irrigation water to mitigate dry spells and increase agricultural and livestock productivity. This study is regarded as a blueprint for planning sustainable water management in the Mandara Mountains.